La motivación en el proceso de enseñanza – aprendizaje de una lengua en peligro. El caso del aragonés - Campos, I.O. (2017)
Over the last century there has been an important paradigm change in Education. In the case of Didactics of Language, this fact has favored the comprehension of the language learning process from a multifactorial view where some concepts like attitudes or motivation, not considered previously, are now understood as key factors. With the aim of contributing in this field in the case of threatened languages, we developed a quasi-experimental research focused on the influence of the use of the minority language as a medium of instruction. Results show that this way of teaching increases the motivation of children in order to learn their mother tongue and it also stimulates the use of the threatened language among them.